Reconsidering the role of drugs in Spanish prisons: a preliminary ethnographic reflection. Issue 3 (26th August 2014) - Briggs, Daniel; Ramiro Pérez Suárez, Jorge
Abstract : Purpose: – The authors thought of the idea for this exploratory paper for Drugs and Alcohol Today after visiting a local prison on the outskirts of Madrid from which these field notes are taken. The authors have also had informal conversations with the contacts working in the Spanish Prison service. When the authors looked at some of the literature around the relationships between drugs and prisons in Spain, the authors found lots of statistics, and material which either said there were lots of drugs in prison or literature which presented over-medicalised processes of drug treatment. In short, the authors found few studies which could bring to life the kind of problems drugs bring to the prison and how the dynamics of the prison are not only directly impacted by drug use but also as drug dealing/trafficking. The paper aims to discuss these issues. Design/methodology/approach: – What the authors offer is only really to draw your attention to the issue. The authors have no real methodology to reflect on other than one of us is an experienced participant observer and the other is a lawyer and criminologist who has worked with numerous clients processed for drug offences in and around prisons in Madrid. Between us, we have undertaken six visits to Madrileñas prisons. Findings: – In this explorative paper the authors want to do three things. First, draw attention to the extent of problem of drugs in prison in Spain. Second, the authors want to suggest that the role drugs needs reconsideration as it plays a pivotal role in the functioning of the prison. Lastly, the authors push for more research into this issue which goes beyond conventional surveys and unnecessary complex regression analyses and instead takes a qualitative approach using observational data and informal conversations to explore these dynamics in more detail. Originality/value: – First, that there is an urgent need to go beyond these official statistics and explore in some nuanced detail about the prison experience in Spain. The existing research is limiting in that it talks tiresomely about the numbers incarcerated and fails to admit the significance of drugs not only as a motivating factor for incarceration but also the role drugs play in the prison environment. The authors need to consider as much the changing demography of Spanish prisons – for example more immigrants, different drugs, etc. – as the everyday experience of drugs, debt, disagreements and violence and how they intersect as a lived experience rather than consider them as separate issues of analysis, dormant from the interconnectedness of the micro-interactions of the prison environment and the respective institutional power structures. The key to this debate, and the general messages of this paper, is to realize a study which can explore the nuances of the role and function of drugs play in Spanish prisons.